2021
DOI: 10.1016/j.ajic.2021.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an antimicrobial surface coating against human coronavirus 229E and SARS-CoV-2

Abstract: The COVID-19 pandemic has accelerated the demand for alternatives to standard cleaning and disinfection practices. Continuously-acting coatings may provide an alternative to common surface treatments. A newly-developed quaternary ammonium polymer coating was applied to stainless steel coupons and evaluated for efficacy against human coronavirus 229E and SARS-CoV-2. The polymer coating reduced levels of both test viruses by greater than 99.9% relative to non-coated stainless steel coupons during a two-hour cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Calfee et al (14) found that seven QAC-based formulations effective against ɸ6 on initial testing were completely ineffective following exposure to wet abrasion cycles in accordance to the US EPA interim guidance (15). Other laboratory studies evaluating QAC-based products have not attempted to assess the durability (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Calfee et al (14) found that seven QAC-based formulations effective against ɸ6 on initial testing were completely ineffective following exposure to wet abrasion cycles in accordance to the US EPA interim guidance (15). Other laboratory studies evaluating QAC-based products have not attempted to assess the durability (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral heavy metals found in nutritional supplements may have some efficacy 136 . Quaternary ammonium compound coatings have attracted study 137,138 . Both anionic polymer and surface calcium bicarbonate generate an antiviral effect based on the extremes of surface pH 79,139 .…”
Section: Coating and Impregnation Barriersmentioning
confidence: 99%
“… 136 Quaternary ammonium compound coatings have attracted study. 137 , 138 Both anionic polymer and surface calcium bicarbonate generate an antiviral effect based on the extremes of surface pH. 79 , 139 Other innovations for fabric or mask impregnation have been cited.…”
Section: Coating and Impregnation Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer-reviewed studies evaluating the effectiveness of QAC-based surface coating treatments against viruses are currently limited. A quaternary ammonium polymer coating applied to stainless steel coupons demonstrated greater than 99.9% (>3 log 10 ) reduction during 2 hours of contact against SARS-CoV-2 and human coronavirus 229E in the presence of 5% organic soil, although wear testing was not performed to assess residual antiviral activity [22]. Another study evaluating a QAC applied onto acrylic surfaces against subsequent SARS-CoV-2 and human coronavirus 229E contamination events demonstrated rapid inactivation upon contact (>90% [>1 log 10 ] reduction); however, just one cleaning event of the coating using a water-based detergent and microfiber cloth substantially reduced product efficacy [23].…”
Section: Tablementioning
confidence: 99%